OPTIMALISASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN ASESMEN DIAGNOSTIK PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Judding, Juwita; Marwiyah, St.; Hisbullah, Hisbullah; Ulfa, Maulidani (Journal of Teaching dan Learning Research, 2025)
This thesis discusses the Optimization of Islamic Religious Education Learning Through the Implementation of Diagnostic Assessment in the Independent Curriculum for Grade V of SDN 360 Pintoe, Luwu Regency, to determine the Diagnostic Assessment process in Islamic religious education learning in the independent curriculum for Grade V at SDN 360 Pintoe, Luwu Regency, and the opportunity and challenge factors for implementing diagnostic assessment in Islamic religious education teaching in the independent curriculum for Grade V at SDN 360 Pintoe, Luwu Regency. This research uses a qualitative approach. The subjects in this study include the principal, teachers, and students. Data were collected through interviews and documentation, with data analysis conducted in stages that included data condensation, presentation, and verification to ensure the validity of the data. Checks were carried out using triangulation techniques. This study found that 1) Diagnostic Assessment in Islamic Religious Education (PAI) learning in the Independent Curriculum at SDN 360 Pintoe serves to identify the needs and potential of students. Through tests, observations, and questionnaires, teachers can design more effective learning strategies. 2) Implementing diagnostic assessments faces challenges in adapting students to project-based learning. However, the flexibility of the Independent Curriculum allows for adjustments to meet student needs, supporting differentiated learning with remedial or enrichment interventions. Constraints such as limited time, resources, and teacher understanding need to be addressed to enhance the effectiveness of diagnostic assessments in supporting student competencies inclusively.